Role of Environmental Awareness in the Application of Environmental Accounting Disclosure in Tourism and Hotel Companies and its Impact on Investor’s Decisions in Amman Stock Exchange - Saleh, Mousa Mohammad Abdullah; Jawabreh, Omar A. A. (International Journal of Energy Economics and Policy, 2020)
The present study aims at examining the level of environmental awareness in the management of tourism and hotels companies listed in the Amman Stock Exchange, its role in the application of environmental accounting disclosure, and to examine the impact of investment decisions on environmental accounting disclosure. To achieve this objective, a sample is chosen from two categories: tourism and hotels management category which consists of 12 financial managers and a major accountant in those companies, and the category of investors in these industrial companies which consists of 47 investors are randomly selected. In order to collect the data, a questionnaire is distributed to each of the hospitality companies and investors in these companies. The study shows that there is a good level of environmental awareness among the management of companies. However, there is a fear of applying the environmental accounting disclosure due to the lack of certainty of the importance of application and the benefits of it, and the lack of appropriate qualification of accountants to apply environmental accounting disclosure. The study shows that there is a real presence of environmental legislation, but there is a large deficiency in the activation of such legislation. Keywords: Environmental Accounting, Amman Stock Exchange, environmental awareness , JEL Classifications: Q56,R 50,Q0 DOI: https://doi.org/10.32479/ijeep.8608